The Effect of Immobilization Stress on Gastric Mucosal Histopathology in White Mice (Mus musculus) Male Swiss Webster Strain - Rizki Bunaya; Ilhami Romus; Fajri Marindra Siregar; Desby Juananda (Molecular and Cellular Biomedical Sciences, 2020)
Background: Immobilization stress is one method of stress induction on experimental animals. It affects the psychology and physical of experimental animals and is the recommended method for assessing changes in histological structure damage. The purpose of research was to analyze the effect of immobilization stress on gastric mucosal in mice.Materials and Methods: This research was experimental with post-test-only control group design. Twenty white mice (Mus musculus) male Swiss Webster strains were used in this study and divided into 4 groups: control, immobilization stress 14 days, immobilization stress 21 days, immobilization stress 28 days. Mice were given immobilization stress using 50 cc syringes for 2 hours every day for 14 days, 21 days and 28 days. Gastric mucosal damage in mice was analyzed under a microscope with of 10 fields of view in each sample. Data were analyzed using the Kruskal Wallis test and Mann Whitney test.Results: Gastric mucosal damage score were 0 in control, 1.42±0.265 in 14 days, 1.82±0.265 in 21 days, and 2.54±0.05 in 28 days. There was significant difference between each group (p<0.05), while the greatest damage was found in the 28 days group.Conclusion: These result indicated that immobilization stress caused gastric mucosal damage and the degree of damage is in accordance with duration of stress.Keywords: gastric mucosal, immobilization, stress